Cross-Domain Edge Computing Offloading Strategy for Delay-Optimized in Low Earth Orbit Satellite Network - YANG Guisong; HUANG Yechao; HE Xingyu (天地一体化信息网络, 2025)
With the rapid development of satellite networks, edge computing on low earth orbit (LEO) satellites has been widely adopted to reduce latency and enhance task processing efficiency. Existing approaches primarily employ centralized or distributed management, where the former suffers from high information collection latency and limited flexibility, while the latter incurs high inter-satellite collaboration costs, restricting global optimization. To address these challenges, an edge computing offloading process based on control domain partitioning is designed, and a latency-optimized cross-domain computing offloading strategy using the Actor-Critic algorithm is proposed. This strategy enables efficient task scheduling and dynamic optimization across computing control domains. Simulation results show that the proposed approach significantly reduces task processing latency and improves task completion rates, demonstrating its applicability and performance advantages in complex LEO satellite networks.